Influence of Glucose Availability and CRP Acetylation on the Genome-Wide Transcriptional Response of Escherichia coli: Assessment by an Optimized Factorial Microarray Analysis - Guebel, Daniel V.; Torres, Néstor V. (Frontiers in Microbiology, 2018)
While in eukaryotes acetylation/deacetylation regulation exerts multiple pleiotropic effects, in E.coli it seems to be more limited and less known. Hence, we aimed to progress in the characterization of this regulation by dealing with three convergent aspects: the effector enzymes involved, the master regulator CRP, and the dependence on glucose availability. The transcriptional response of E. coli BW25113 was analysed across 14 relevant scenarios. These conditions arise when the wild type and four isogenic mutants (defective in deacetylase CobB, defective in N(epsilon)-lysine acetyl transferase PatZ, Q- and R-type mutants of protein CRP) are studied under three levels of glucose availability (glucose-limited chemostat and glucose-excess or glucose-exhausted in batch culture). The Q-type emulates a permanent stage of CRPacetylated, whereas the R-type emulates a permanent stage of CRPdeacetylated. The data were analysed by an optimized factorial microarray method (Q-GDEMAR). By analysing one mutant against the other, we were able to unravel the true genes that participate in the interaction between (Delta)cobB/(Delta)patZ mutations and glucose availability. Increasing stages of glucose limitation appear to be associated with the up-regulation of specific sets of target genes rather than with the loss of genes present when glucose is in excess. Both CRPdeacetylated and CRPacetylated produce extensive changes in specific subsets of genes, but their number and identity depend on the glucose availability. In other sub-sets of genes, the transcriptional effect of CRP seems to be independent of its acetylation or deacetylation. Some specific ontology functions can be associated with each of the different sets of genes detected herein. CRP cannot be thought of only as an effector of catabolite repression, because it acts along all the glucose conditions tested (excess, limited, and exhausted), exerting both positive and negative effects through different sets of genes. Acetylation of CRP does not seem to be a binary form of regulation, as there is not a univocal relationship between its activation/inhibitory effect and its acetylation/deacetylation stage. All the combinatorial possibilities are observed. During the exponential growth phase, CRP also exerts a very significant transcriptional effect, mainly on flagellar assembly and chemotaxis (FDR = 7.2x10-44).